The mediating effect of self-efficacy in the relationship between communication skills and practices of preventing infectious diseases among daycare center teachers in South Korea - Jieun Shin (Korean Academy of Child Health Nursing, 2021)
Purpose This study investigated the practices of preventing infectious diseases by daycare center teachers. The focus was on the mediating effects of self-efficacy in the relationship between communication skills and practices of preventing infectious diseases. Methods This study used a descriptive correlational design. The participants were 164 daycare center teachers. Hierarchical regression was used to test the mediating effect of self-efficacy in the relationship between communication skills and practices of preventing infectious diseases. Data were analyzed using the independent t-test, one-way analysis of variance, Pearson correlation coefficients, and hierarchical regression. The mediation effect was analyzed using an SPSS Macro program, PROCESS. Results Significant relationships were found between communication skills and practices of preventing infectious diseases (β=.19, p<.001), self-efficacy and practices of preventing infectious diseases (β=.59, p<.001), and communication skills and self-efficacy (β=.27, p<.001). Self-efficacy had a significant mediating effect (β=.17, 95% confidence interval=0.07-0.29) on practices of preventing infectious diseases. Conclusion In order to improve practices of preventing infectious diseases among daycare teachers, it is necessary to develop and apply interventions and methods that can increase effective communication skills and self-efficacy.